A perspective on biodegradable polymer biocomposites - from processing to degradation - Bronwyn Laycock; Steven Pratt; Peter Halley (Functional Composite Materials, 2023)
Abstract Given the greater global awareness of environmental impacts of plastics and the need to develop alternative materials from renewable natural resources, there has been an increasing drive over recent years to develop biobased and biodegradable composites, especially those produced from agro-industrial waste and byproducts. This perspective provides a brief introduction to the field as well as discussing some of the critical aspects to be considered as we accelerate the development of these novel alternative materials for a range of applications.